Family ties and corporate tax avoidance - Niu, Geng; Wang, Yi; Zhou, Yang; Gan, Xu (Journal of International Business Studies, 2024)
A well-established body of international business research examines how the institutional environment influences corporate decisions. We add to this literature by investigating the unexplored link between family, a fundamental institution in human society, and corporate tax decisions. Applying theories on social norms and the evolution of moral boundaries, we argue that the strength of family ties in a society increases corporate tax avoidance by narrowing the scope of moral responsibilities. We confirm this argument by conducting regression analyses using a large sample of firms from 44 countries. In addition, the positive effect of family ties on tax avoidance is attenuated for firms in countries with inclusive political institutions and is amplified for family firms. Using a sample of U.S. companies, we also find that firms avoid more taxes when they are located in states with stronger family ties and when their CEOs are from countries with stronger family ties, indicating that both the social norms that surround firms and those that are embedded in the origin countries of the managers affect firm tax decisions. Our study implies that the institution of family provides a valuable perspective to understand the international differences in corporate behaviors.